Tin whiskers behaviour on immersion tin surface finish at high temperature and humidity condition - Fadil, N. A. (2015)
Towards green technology application in electronic industry, pure tin as a Pb-free component lead finish become a popular choice, yet facing the problem with tin whisker formation. Tin whisker has turned into a serious concern in the electronic industry where it may cause short circuit to electronic components. It has been long believed that residual stress generated by external stresses, internal stresses, and temperature is the root cause of whisker formation. In this study, the effect of temperature and humidity on the formation and growth of tin whiskers was studied focusses on immersion tin surface finish only. The samples were prepared by a chloride-based bath and held at 30°C/ 60% RH (normal condition) and 55°C/ 85%RH (severe condition) for several time intervals. The morphology of tin whiskers on an immersion tin finish on copper substrate was observed by FESEM. The whiskers length was measured using JEDEC-Standard JESD22-A121A. The results showed that, tin whiskers formed in various types including nodules, straight, twist, bent, and spiral shape with striations along its circumference for normal condition, but only nodule- and spiral-type of whiskers only can be observed for severe conditions. Surprisingly, normal condition produce longer whiskers length as compared to the whiskers formed when the surface exposed to the severe condition.